УПРОСТИТЬ!!!! СРОЧНО НУЖНО :) 1) (x+6)^2-x^2 2) (2x-6)^2-4x^2 3) (3x-1)^2-9x^2 4) (6x+2)^2-36x^2

УПРОСТИТЬ!!!! СРОЧНО НУЖНО :) 1) (x+6)^2-x^2 2) (2x-6)^2-4x^2 3) (3x-1)^2-9x^2 4) (6x+2)^2-36x^2
Гость
Ответ(ы) на вопрос:
Гость
1) (x+6)²-x²=x²+12x+36-x²=12x+36=12(x+3) 2) (2x-6)²-4x²=4x²-24x+36-4x²=-24x+36=36-24x=12(3-2x) 3) (3x-1)²-9x²=9x²-6x+1-9x²=-6x+1=1-6x 4) (6x+2)²-36x²=36x²+24x+4-36x²=24x+4=4(6x+1)
Гость
1) [latex] (x+6)^{2} - x^{2} [/latex]=[latex] x^{2} +12x+12- x^{2} =12x+12[/latex]=[latex]12(x+3)[/latex] 2) [latex] (2x-6)^{2} - 4x^{2} = 4x^{2} - 24x+36 - 4x^{2} = -24x+36[/latex]=[latex]12(-2x+3)[/latex] 3)[latex] (3x-1)^{2} - 9x^{2}= 9x^{2}-6x+ 1^{2} - 9x^{2} = -6x+1[/latex] 4)[latex] (6x+2)^{2} - 36x^{2} = 36x^{2}+24x+4- 36x^{2} = 24x+4[/latex]=[latex]4(6x+1)[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы